2016
DOI: 10.1093/cid/ciw668
|View full text |Cite
|
Sign up to set email alerts
|

Definitions of Cytomegalovirus Infection and Disease in Transplant Patients for Use in Clinical Trials: Table 1.

Abstract: Cytomegalovirus (CMV) infection and disease are important causes of morbidity and mortality in transplant recipients. For the purpose of developing consistent reporting of CMV outcomes in clinical trials, definitions of CMV infection and disease were developed and most recently published in 2002. Since then, there have been major developments in its diagnosis and management. Therefore, the CMV Drug Development Forum consisting of scientists, clinicians, regulators, and industry representatives has produced an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
745
2
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 783 publications
(762 citation statements)
references
References 12 publications
2
745
2
13
Order By: Relevance
“…Moreover, Madi N et al found in renal transplant patients with symptomatic CMV infection the CMV-DNA in serum were all more than 6.5 × 10 4 copies/mL. While at present, only a few studies have evaluated a cut-off value for CMV-DNA in BALF [29, 30]. Drew et al has reported that CMV DNA levels of >5 × 10 5 copies/mL in the patient’s BALF confirmed the presence of CMV pneumonia [31], and Boeckh et al found that CMV viral load > 500 IU/ml in BALF was likely to represent CMV pneumonia in hematopoietic stem cell transplantation patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Madi N et al found in renal transplant patients with symptomatic CMV infection the CMV-DNA in serum were all more than 6.5 × 10 4 copies/mL. While at present, only a few studies have evaluated a cut-off value for CMV-DNA in BALF [29, 30]. Drew et al has reported that CMV DNA levels of >5 × 10 5 copies/mL in the patient’s BALF confirmed the presence of CMV pneumonia [31], and Boeckh et al found that CMV viral load > 500 IU/ml in BALF was likely to represent CMV pneumonia in hematopoietic stem cell transplantation patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore prophylaxis against CMV is no longer in use 7, 8. Moreover early preemptive antiviral therapy may lead to an increase of CMV disease after day 100 post transplantation 9.…”
Section: Introductionmentioning
confidence: 99%
“…EOD for CMV was defined by standard criteria 11 . HHV-6 encephalitis was defined as clinical encephalitis supported by compatible radiographic findings by magnetic resonance imaging in the setting of simultaneous HHV-6 viremia 12 .…”
Section: Methodsmentioning
confidence: 99%